Wybrane zagadnienia wysokowydajnej obróbki mechanicznej - Feldshtein, Eugene; Leksycki, Kamil (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This book is composed with five chapters, which consider the general issues of work productivity and the factors affecting it, the current state and development of CNC machines, cutting tools, machining holders and the possibilities of measurements automation, which all together provide a significant increase in the efficiency of mechanical production. This book is a textbook for students of Mechanical Engineering degree course, and can also be useful for students of Manufacturing Management and Engineering degree course.
Keywords: obróbka wysokowydajna; wydajność pracy; rozwój maszyn CNC; wysokowydajne narzędzia skrawające; efektywne oprzyrządowanie technologiczne; automatyzacja pomiarów; high-performance machining; work productivity; CNC machines development; high-performance cutting tools; effective technological fixtures; measurement automation; maszyny i narzędzia skrawające; obrabiarka sterowana komputerowo; obróbka ubytkowa; uchwyt obróbkowy